Conditioning factors for labor participation in persons with disability due to spine lesions attended at a specialized rehabilitation center - Casallo Castilla, Carmen Natividad (2023)
Objective: To determine the conditioning factors for labor participation in persons with disability due to spine lesions attended at a specialized rehabilitation center. Methods: A retrospective observational study was carried out at the Departamento de Investigación, Docencia, y Atención en Ayuda al Tratamiento del Servicio de Rehabilitación Profesional from 2016 to 2019, 224 patients were evaluated. Clinical, sociodemographic and contextual variables were collected as well as economic activity before and after the trauma. Results: 65% of patients were males; mean age was 38.61 ± 13.33; 85.3% had paraplegia and 63.5% had a lesion grade A on the ASIA scale; duration of illness was higher than one year in 30.4%; 52.2% were single; 51.3% come from provinces of Peru; 50.9% had secondary school level and 61% lived in extreme poverty. A significative difference for labor participation was found between sex (p<0.01) and labor condition (p<0.014) before the spinal lesion. Labor participation after the spinal lesion correlated with socioeconomic level (p<0.005) and the degree of the lesion based on the ASIA scale (p<0.014). The logistic regression analysis found that only duration of illness correlated with labor participation (p=0.039; OR=19.9). Conclusions: Patients with spinal lesions who lived in extreme poverty had higher labor participation as well as those with higher scores in the ASIA scale. The only predicting factor for labor participation was duration of illness.